2022
DOI: 10.1002/jcsm.13104
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical study on the mechanisms underlying critical illness myopathy—A time‐course approach

Abstract: Background Critical illness myopathy (CIM) is a consequence of modern critical care resulting in general muscle wasting and paralyses of all limb and trunk muscles, resulting in prolonged weaning from the ventilator, intensive care unit (ICU) treatment and rehabilitation. CIM is associated with severe morbidity/mortality and significant negative socioeconomic consequences, which has become increasingly evident during the current COVID-19 pandemic, but underlying mechanisms remain elusive. Methods Ten neuro-ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Muscle biopsies from critically ill patients revealed an overall decrease in mtDNA content and a downregulation of many genes orchestrating mitochondrial function [ 90 , 161 ]. This was also recently confirmed in patients with CIM [ 77 ]. Especially genes for mitochondrial fusion and replication, such as PGC1α, MFN2 and OPA1, seem to be affected in skeletal muscles [ 102 , 114 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...supporting
confidence: 68%
See 2 more Smart Citations
“…Muscle biopsies from critically ill patients revealed an overall decrease in mtDNA content and a downregulation of many genes orchestrating mitochondrial function [ 90 , 161 ]. This was also recently confirmed in patients with CIM [ 77 ]. Especially genes for mitochondrial fusion and replication, such as PGC1α, MFN2 and OPA1, seem to be affected in skeletal muscles [ 102 , 114 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...supporting
confidence: 68%
“…Although the majority of studies were able to mimic certain pathophysiological aspects, it has been found that the combined effect and prolonged application of some methods was best suited to replicate predominant myosin loss, decreased compound muscle action potentials and normal nerve conduction velocities, similar to patients with CIM [ 69 , 74 , 75 ]. In this context, porcine animal models of critical illness revealed marked downregulations in mitochondrial gene expression controlling the PGC1-family, the ETC enzyme complexes and several metabolic pathways [ 73 , 76 ], matching at least in part with the results of patients with CIM [ 77 , 78 ]. Although not covering all methodical aspects of a fully grown ICU animal model, studies investigating mitochondrial function by pure immobilization [ 52 , 53 , 54 ], denervation [ 47 , 49 , 59 ] or sepsis [ 79 , 80 ] also show deficits in mitochondrial structure and function comparable to observations in critically ill patients, including mitochondrial swelling, decreased mitochondrial content and downregulation of PGC1α mRNA expression as well as several mitochondrial metabolic pathways [ 81 , 82 , 83 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Septic patients often develop intensive care unit‐acquired weakness (ICUAW), which is accompanied by muscle‐mass loss, increased morbidity, and mortality 1,2 . ICUAW is defined as ‘clinically detected weakness in critically ill patients in whom there is no plausible aetiology other than critical illness’ 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Septic patients often develop intensive care unit-acquired weakness (ICUAW), which is accompanied by muscle-mass loss, increased morbidity, and mortality. 1,2 ICUAW is defined as 'clinically detected weakness in critically ill patients in whom there is no plausible aetiology other than critical illness'. 3 Patients with ICUAW are classified into those with critical illness myopathy (CIM), critical illness polyneuropathy (CIP), or a combination of both.…”
Section: Introductionmentioning
confidence: 99%